Monitoring Balloon Test Occlusion of the Internal Carotid Artery with Transcranial Doppler: A Case Report and Literature Review. Issue 1 (February 2014) - Galego, Orlando; Nunes, César; Morais, Ricardo; Sargento-Freitas, João; Sales, Francisco; Machado, Egídio
Angiographic balloon test occlusion (BTO) allows preoperative risk evaluation of patients undergoing permanent therapeutic occlusion of the internal carotid artery (ICA). The sensitivity of the BTO can be increased using different complementary techniques. Transcranial Doppler (TCD) stands out as a non-invasive, bedside method providing real-time monitoring of cerebral haemodynamics, therefore accurately identifying patients at risk of stroke. A case of a 30-year-old woman with a giant intracavernous aneurysm of the left ICA presenting with subacute left VI nerve palsy is described. A pre-operative TCD- and EEG-monitored BTO of the left ICA was performed. The 16.7% drop found in the middle cerebral artery's peak systolic velocity (PSVMCA ) predicts clinical and haemodynamic tolerance to the permanent loss of that vessel. This case illustrates the potential of TCD monitoring during temporary BTO of the ICA. It highlights its ability to provide a complete preclinical evaluation of collateralization and autoregulatory adaptation to unilateral ICA occlusion. TCD may also decrease the time of occlusion required for the BTO.